ACO Clinicians Have Higher Medicare Part B Medical Services Payments Than MIPS Clinicians Under the Quality Payment Program - Mina Shrestha PhD; Hari Sharma PhD; Keith J. Mueller PhD (SAGE Publishing, 2024)
The Quality Payment Program (QPP) is a Medicare value-based payment program with 2 tracks: -Advanced Alternative Payment Models (A-APMs), including two-sided risk Accountable Care Organizations (ACOs), and Merit-based Incentive Payment System (MIPS). In 2020, A-APM eligible ACO clinicians received an additional 5% positive, and MIPS clinicians received up to 5% negative or 2% positive performance-based adjustments to their Medicare Part B medical services payments. It is unclear whether the different payment adjustments have differential impacts on total medical services payments for ACO and MIPS participants. We compare Medicare Part B medical services payments received by primary care clinicians participating in ACO and MIPS programs using Medicare Provider Utilization and Payment Public Use Files from 2014 to 2018 using difference-in-differences regressions. We have 254 395 observations from 50 879 unique clinicians (ACO = 37.86%; MIPS = 62.14%). Regression results suggest that ACO clinicians have significantly higher Medicare Part B medical services payments ($1003.88; 95% CI: [579.08, 1428.69]) when compared to MIPS clinicians. Our findings suggest that ACO clinicians had a greater increase in medical services payments when compared to MIPS clinicians following QPP participation. Increased payments for Medicare Part B medical services among ACO clinicians may be driven partly by higher payment adjustment rates for ACO clinicians for Part B medical services. However, increased Part B medical services payments could also reflect clinicians switching to increased outpatient services to prevent potentially costly inpatient services. Policymakers should examine both aspects when evaluating QPP effectiveness.